Labour Manoeuvrability and Economic Performance in Township-Village Enterprises: The Case of China - Eelco Modderman; Cees Gorter; Jasper Dalhuisen; Peter Nijkamp (Tinbergen Institute, 2001)
The purpose of this paper is to explain the relationship between economic performance and labourmanoeuvrability of township-village enterprises in the Jiangsu province, China. We start with a generaloverview of the development in the Chinese economy and the functioning of labour markets. Next, weperform a statistical analysis on economic performance and labour market behaviour based on a sampleof 103 enterprises. The flexibility to fire employees turns out to have a considerable impact on growth inadded value of the enterprises, whereas hiring flexibility appears to have negligible effects.
Keywords: 330; Ländliches Kleingewerbe; Ländliche Industrie; Sozialistisches Unternehmen; Unternehmenserfolg; Arbeitsmobilität; China